PROBLEMS OF YEAR-ROUND MICROPROPIATION OF STRAWBERRY AND NEW APPROACHES TO THEIR SOLUTION - Sergey A. Kornatskiy (Siberian Journal of Life Sciences and Agriculture)
Clonal micropropagation of strawberries can significantly accelerate the start of mass use of new highly productive cultivars. Mostly such material is needed for planting nurseries. However, the discrepancy between the annual working rhythm of the laboratory and the culture development cycle in natural conditions requires solving the problems of ensuring the viability of microplants during the period from late August to early March before planting in the greenhouse. At this time, it is often impossible to provide adequate conditions for the adaptation of microplants due to the low influx of sunlight and the high cost of using artificial sources.